Application of Principal Component Analysis of Sows' Behavioral Indicators of the Welfare Quality® Protocol to Determine Main Components of Behavior - Friedrich, Lena; Krieter, Joachim; Kemper, Nicole; Czycholl, Irena (Frontiers in Animal Science, 2021)
Understanding behavior is important in terms of welfare assessments to be able to evaluate possible changes in behavior among different husbandry systems. The present study applied principal component analysis (PCA) to reveal relationships between behavioral indicators to identify the main components of sows’ behavior promoting feasibility of welfare assessments by providing possibilities for variable reduction and aggregation. The indicators of the Welfare Quality® protocol’s principle to assess behavior were repeatedly applied by two observers on 13 farms in Northern Germany. This included Qualitative Behavior Assessments (QBA) to evaluate animals’ body language using 20 pre-defined adjectives, assessments of social and exploratory behavior, stereotypies, and human-animal relationship tests. Two separate PCA were performed with respect to the QBA: (1) adjectives were included as independent variables and (2) adjectives were pre-aggregated using the calculation rules of the Welfare Quality® protocol for fattening pigs since a calculation for sows does not yet exist. In both analyses, two components described sows’ behavior. Most variance was explained by the solution with adjectives as independent variables (51.0 %). Other behavioral elements not captured as indicators by the protocol may still be important for all-inclusive welfare assessments as the required variance of 70% was not achieved in the analyses. Component loadings were used to determine components’ labels as (1) ‘satisfaction of exploratory behavior’ and (2) ‘social resting’. Both components reflected characteristics of sows’ natural behavior and can subsequently be used for variable reduction but also for development of component scores for aggregation. As defined for PCA, component 1 explained more variance than component 2. PCA is useful to determine the main components of sows’ behavior, which can be used to enhance feasibility of welfare assessments.